The Role of Masked Solutions in the Accuracy of an Insight Problem-Solving Task - Puvia, Elisa; Taibi, Davide; Tressoldi, Patrizio (Journal of Anomalous Experience and Cognition, 2022)
The primary aim of the study was to test the alleged facilitating role of insight-like strategy in the detection of masked solutions Compound Remote Associates problems (CRA). A sample of 114 participants solved 19 CRA problems presented online. Participants were requested to solve the problems in which either the solution to the CRA was randomly presented in a masked condition or no solution was provided. After each trial participants were requested to report whether they had used insight or analytical strategy, and were also required to complete a sensation seeking scale and a measure of creativity. The results showed a small, but robust correlation between the CRA problems accuracy and the degree of insight type strategy used for their solution. The degree of sensation seeking, the score in creativity, and the outcome of the manipulation check did not reveal any influence on the CRA problems solution. The use of intuitive strategies may facilitate psirelated creative problem solving, but confirmatory research is needed.